The Continuity of Pre-Islamic Motifs in Javanese Mosque Ornamentation, Indonesia - Lee-Niinioja, Hee Sook (Archaeopress, 2022)
This book assesses the continuity and significance of Hindu-Buddhist design motifs in Islamic mosques in Java. The volume investigates four pre-Islamic motifs in Javanese mosque ornamentation from the 15th century to the present day: prehistoric tumpals, Hindu-Buddhist kala-makaras, lotus buds, and scrolls.